EmQuestão Vol. 18, n. 2 (2012) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
EmQuestão Vol. 18, n. 2 (2012)Link de acesso ao númerohttp://seer.ufrgs.br/index.php/EmQuestao/issue/view/1962/showToc